Hippocratic, Religious, and Secular Medical Ethics : The Points of Conflict - Veatch, Robert M. (Book collections on Project MUSE., 2012)
Where should physicians get their ethics? Professional codes such as the Hippocratic Oath claim moral authority for those in a particular field, yet according to medical ethicist Robert Veatch, these codes have little or nothing to do with how members of a guild should understand morality or make ethical decisions. While the Hippocratic Oath continues to be cited by a wide array of professional associations, scholars, and medical students, Veatch contends that the pledge is such an offensive code of ethics that it should be summarily excised from the profession. What, then, should serve as a b.